Flexible Model Proposals for Post-Disaster Temporary Housing in Architectural Design - Mazlum Kalak; Ozge Zenter; Emine Fulya Özmen (Journal of Design for Resilience in Architecture and Planning)
Shelter is one of the most basic needs that emerged with the existence of humanity and is necessary for people to continue their lives. In addition to meeting physical needs, it also has social and cultural functions. Especially in the post-disaster process, it is essential to create temporary shelter units in the face of emerging problems. Since societies can be affected simultaneously in this process, needs must be met as quickly as possible. "Flexible container designs" are seen as a solution to this problem. Flexible container designs can provide significant advantages in meeting basic needs after a disaster and in terms of rapid intervention. The study aims to present flexible model suggestions that can be used to produce temporary shelter units. Because the production of temporary shelter units is essential in terms of flexibility due to reasons such as reusability, portability, limited design periods, etc. The study discusses the designs made by the students within the scope of the Structural System Information course of the Architecture Department of Gazi University Faculty of Architecture. The students were asked to produce solutions to problems such as the emergence of shelter needs for people after disasters, bringing containers to the need area, and serving different functions. The study reveals the value of the concepts of flexibility, portability, and modularity in the design of temporary shelter units through student designs; it emphasizes the importance of these concepts in design processes in both architectural education and architectural practices. The study will contribute to the development of innovative, flexible, and portable solutions.